Alcohol marketing and youth alcohol consumption: a systematic review of longitudinal studies published since 2008. (8th November 2016) - Jernigan, David; Noel, Jonathan; Landon, Jane; Thornton, Nicole; Lobstein, Tim
Abstract: Background and Aims: Youth alcohol consumption is a major global public health concern. Previous reviews have concluded that exposure to alcohol marketing was associated with earlier drinking initiation and higher alcohol consumption among youth. This review examined longitudinal studies published since those earlier reviews. Methods: Peer‐reviewed papers were identified in medical, scientific and social science databases, supplemented by examination of reference lists. Non‐peer‐reviewed papers were included if they were published by organizations deemed to be authoritative, were fully referenced and contained primary data not available elsewhere. Papers were restricted to those that included measures of marketing exposure and alcohol consumption for at least 500 underage people. Multiple authors reviewed studies for inclusion and assessed their quality using the National Heart, Lung and Blood Institute's Quality Assessment Tool for Observation Cohort and Cross‐Sectional Studies. Results: Twelve studies (ranging in duration from 9 months to 8 years), following nine unique cohorts not reported on previously involving 35 219 participants from Europe, Asia and North America, met inclusion criteria. All 12 found evidence of a positive association between level of marketing exposure and level of youth alcohol consumption. Some found significant associations between youth exposure to alcohol marketing and initiation of alcohol use (odds ratios ranging from 1.00 to 1.69), and there were clear associations between exposure and subsequent binge or hazardous drinking (odds ratios ranging from 1.38 to 2.15). Mediators included marketing receptivity, brand recognition and alcohol expectancies. Levels of marketing exposure among younger adolescents were similar to those found among older adolescents and young adults. Conclusions: Young people who have greater exposure to alcohol marketing appear to be more likely subsequently to initiate alcohol use and engage in binge and hazardous drinking.